Miracle man : the story of Jesus - Hendrix, John, 1976- (Abrams Books for Young Readers, 2016)
"This picture book written and illustrated by John Hendrix focuses on the Biblical accounts of miracles performed by Jesus and concludes with the Crucifixion and the Resurrection. There is a detailed author's note and a list of Biblical passages."--